Kulintangan / Adsone Matthew Mitty Gabu - Mitty Gabu, Adsone Matthew (2007)
Modem music in Malaysia is a rapidly growing industry. Its development has been revolutionary, as talented musician from diverse cultural background have drawn on their rich heritages to create new forms using a combination of traditional and western instruments. Malaysia has a great potential for making an impact in the international arena by promoting its rich and developing musical heritage. SABAH, one of the 13 states of Malaysia located on the worlds’ third largest island, Borneo. In Sabah, traditional music is an integral part of the cultural life of the people. With around fifty ethnic communities, this state has a multitude of traditional vocal and instruments musical genres. Music is part of daily life, as well as ritual practices associated with rites of passages, traditional warfare, healing and rice cultivating.